PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA - WITA ROSWITA WITA ROSWITA; SURYANA SURYANA; KASINO MARTOWINANGUN KASINO MARTOWINANGUN (POLITEKNIK PIKSI GANESHA, 2018)
This study aims to determine how the organizational culture and employee engagement on turnover The main focus of the researcher is on how attachment of employees of PT. Industri Telekomunikasi Indonesia (Persero) Bandung Towards. This research uses descriptive method and verifikatif. The population in this study is 495, because the population exceeds 100, the samples taken as many as 91 employees of PT. Industri Telekomunikasi Indonesia (Persero) Bandung. Technical analysis is used is the pearson product moment correlation coefficient and multiple regression analysis. The result of research shows that organizational culture and compensation are in high category, while job satisfaction is in the medium category. The result showed correlation calculation organizational culture variables with job satisfaction relationship with a medium classification. while the compensation to the job relationship with a high classification At Adjusted R Square values, job satisfaction is influenced by organizational culture and compensation is in the medium classification.